Maintenance valine, isoleucine, and tryptophan requirements for poultry - Lima, M. B. de [UNESP]; Sakomura, N. K. [UNESP]; Dorigam, J. C. P. [UNESP]; Silva, E. P. da [UNESP]; Ferreira, N. T. [UNESP]; Fernandes, J. B. K. [UNESP] (Oxford Univ Press, 2016)
Poultry maintenance requirements for valine, isoleucine, and tryptophan were measured by nitrogen balance using different unit systems. The nitrogen balance trial lasted 5 d with 48 h of fasting (with roosters receiving only water + sucrose) and the last 72 h for feeding and excreta collection. Forty grams of each diet first-limiting in valine, isoleucine, or tryptophan was fed by tube each day (3 d) to give a range of intakes from 0 to 101, 0 to 119, and 0 to 34 mg/kg BW d of valine, isoleucine, and tryptophan, respectively. A nitrogen-free diet containing energy, vitamins, and minerals, meeting the rooster requirements, was offered ad libitum during these three d. To confirm that the amino acids studied were limiting, a treatment was added with a control diet formulated by adding 0.24 g/kg of L-valine, 0.21 g/kg of L-isoleucine, and 0.10 g/kg of L-tryptophan to the diets with lower amino acid level. Excreta were collected during the last 3 d of the balance period and the nitrogen content of the excreta was analyzed. For each amino acid, a linear regression between nitrogen retention (NR) and amino acid intake was performed. The equations from linear regression were: NR = -98.6 (+/- 10.1) + 2.4 (+/- 0.2) x Val, NR = -46.9 (+/- 7.1) + 2.3 (+/- 0.1) x Ile, NR = -39.5 (+/- 7.7) + 7.3 (+/- 0.4) x Trp; where Val, Ile, and Trp are the intakes of valine, isoleucine, and tryptophan in mg/kg body weight per d, respectively. The valine, isoleucine, and tryptophan required to maintain the body at zero NR were calculated to be 41, 20, and 5 mg/kg body weight per d, respectively. For the system unit mg per kg of metabolic weight, the intake of valine, isoleucine, and tryptophan was 59, 32, and 9, respectively. Considering the degree of maturity of the animal and body protein content (BPm0.73 x u), the amounts of valine, isoleucine, and tryptophan required for maintenance were calculated to be 247, 134, and 37 mg per unit of maintenance protein (BPm0.73 x u) per d. Maintenance requirement is more adequately expressed as body protein content.
Keywords: amino acids; breeder roosters; dilution technique; nitrogen retention; regression equation